Differential Molecular Interactions of Imidacloprid with Dissolved Organic Matter in Citrus Soils with Diverse Planting Ages - Junquan Chen; Yawen Zhang; Yanqi Guo; Kai Jiang; Duo Li; Taihui Zheng (Agriculture)
The interactions between dissolved organic matter (DOM) and agrochemicals (e.g., neonicotinoid insecticides, NIs) govern the distribution, migration, and potential environmental risks of agrochemicals. However, the long-term effects of agricultural management on the DOM components and structure, as well as their further influences on the interactions between DOM and agrochemicals, remain unclear. Here, spectroscopic techniques, including Fourier transform infrared spectroscopy, two-dimensional correlation spectroscopy, and three-dimensional excitation–emission matrix fluorescence spectroscopy were employed to delve into the interaction mechanism between the DOM from citrus orchards with distinct cultivation ages (10, 30, and 50 years) and imidacloprid, which is a type of pesticide widely used in agricultural production. The findings revealed that the composition and structure of soil DOM significantly change with increasing cultivation age, characterized by an increase in humic substances and the emergence of new organic components, indicating complex biodegradation and chemical transformation processes of soil organic matter. Imidacloprid primarily interacts with fulvic acid-like fractions of DOM, and its binding affinity decreases with increasing cultivation age. Additionally, the interactions of protein-like fractions with imidacloprid occur after humic-like fractions, suggesting differential binding behaviors among DOM fractions. These results demonstrate that cultivation age significantly influences the composition and structural characteristics of soil DOM in citrus orchards, subsequently affecting its sorption capacity to imidacloprid. This study enhances the understanding of imidacloprid’s environmental behavior and provides theoretical support for the environmental risk management of neonicotinoid pesticides.